Tinbergen rules the Taylor Rule - Thomas R. Michl (Levy Economics Institute of Bard College, 2006)
This paper elaborates a simple model of growth with a Taylor-like monetary policy rule that includes inflation-targeting as a special case. When the inflation process originates in the product market, inflation-targeting locks in the unemployment rate prevailing at the time the policy matures. Although there is an apparent NAIRU and Phillips curve, this long run position depends on initial conditions; in the presence of stochastic shocks, it would be path dependent. Even with an employment target in the Taylor Rule, the monetary authority will generally achieve a steady state that misses both its targets since there are multiple equilibria. With only one policy instrument, Tinbergen's Rule dictates that policy can only achieve one goal, which can take the form of a linear combination of the two targets.
Keywords: E12; E52; 330; Inflation targeting; employment targeting; Taylor rule; hysteresis